VDAC Genes Expression and Regulation in Mammals - Zinghirino, Federica; Pappalardo, Xena Giada; Messina, Angela; Nicosia, Giuseppe; De Pinto, Vito; Guarino, Francesca (Frontiers in Physiology, 2021)
VDACs are pore-forming proteins coating the mitochondrial outer membrane and playing the role of main regulators for metabolites exchange between cytosol and mitochondria. In mammals, three isoforms have evolutionary originated, VDAC1, VDAC2 and VDAC3. Despite similarity in sequence and structure, evidence suggests different biological roles in normal and pathological conditions for each isoform. We compared Homo sapiens and Mus musculus VDAC genes and their regulatory elements. RNA-seq transcriptome analysis shows that VDAC isoforms are expressed in human and mouse tissues at different levels with a predominance of VDAC1 and VDAC2 over VDAC3, with the exception of reproductive system. Numerous transcript variants for each isoform suggest specific context-dependent regulatory mechanisms. Analysis of VDAC core promoters have highlighted that, both in human and mouse, VDAC genes show features of TATA-less ones. The level of CG methylation of the human VDAC genes revealed that VDAC1 promoter is less methylated than other two isoforms. We found that expression of VDAC genes is mainly regulated by transcription factors involved in controlling cell growth, proliferation and differentiation, apoptosis, bioenergetic metabolism. A non-canonical initiation site termed the TCT/TOP motif, target for translation regulation by mTOR pathway, was identified in human VDAC2 and VDAC3 and in every murine VDACs promoter. In addition, specific TFBSs have been identified in each VDAC promoter supporting the hypothesis that there is a partial functional divergence. These data corroborate our experimental results and reinforce the idea that gene regulation could be the key to understanding the evolutionary specialization of VDAC isoforms.